PODCAST BOCOR ALUS POLITIK’S ROLE IN BUILDING GEN Z'S POLITICAL AWARENESS AHEAD THE 2024 ELECTION - Widuri, Rachma Tri; Moniaga, Ariadne Khatarina (Universitas Mercu Buana, 2025)
This study explores how Tempo Media Group’s Bocor Alus Politik podcast enhances Generation Z’s political awareness as beginner voters in the 2024 Election. Available on Spotify and YouTube, this podcast was designed to meet the visual preferences of young people. Since it’s launch on May 20, 2023, it has launched several episodes which sparked public discussions and opinions towards the political figures. Using the uses and gratifications theory, this qualitative study with in-depth interviews and social media observations finds that Bocor Alus Politik significantly shapes Gen Z’s perception of the 2024 Election, demonstrating social media’s impact on fostering political awareness among young voters.